Application of PEM Fuel Cell for Stand-alone Based on a Fuzzy PID Control - SM Rakhtala; E Shafiee Roudbari (Bulletin of Electrical Engineering and Informatics, 2016)
Due to increasing concerns on environmental pollution and depleting fossil fuels, fuel cell (FC) has received considerable attention as an alternative to the conventional energy systems. Fuel cells have numerous stand-alone and grid-connected applications. This paper presents the control of the stand-alone application based on fuzzy PID (FPID) controller. The aim of the paper is to achieve the control of the fuel cell for stand-alone with suitable power conditioning unit (PCU) that consists of the two stages of DC/DC converter and DC/AC inverter. An analysis of cascade structure based on FPID controller for a single phase inverter is done and comprises two feedback control loops. The inductor current and capacitor voltage are measured and feedback to the inner loop and the outer loop, respectively. The analytical models of the h PEM fuel cells is designed and simulated by developing a detailed simulation software using Matlab, Simulink and SimPowerSystems Blockset for portable applications. The PEM fuel cell model is validated with NexaTM Power Module MAN5100078 by Ballard Power Systems at 80°C. In this paper shown that the proposed controller shows a robust behavior and good transient response.